Ankrd31 in Sperm and Epididymal Integrity - Manfrevola, Francesco; Martinez, Guillaume; Coutton, Charles; Rocco, Domenico; Reynaud, Karine; Le Vern, Yves; Froment, Pascal; Beauclair, Linda; Aubert, Denise; Pierantoni, Riccardo; Chianese, Rosanna; Guillou, Florian (Frontiers in Cell and Developmental Biology, 2021)
Ankyrin proteins (ANKRD) are key mediators linking membrane and sub-membranous cytoskeletal proteins. Recent findings have highlighted a new role of ANKRD31 during spermatogenesis, elucidating its involvement in meiotic recombination and male germ cell progression. Following testicular differentiation, spermatozoa (SPZ) enter into the epididymis, where they undergo several biochemical and enzymatic changes. The epididymal epithelium is characterized by cell-to-cell junctions able to form the blood-epididymal-barrier (BEB). This intricate epithelial structure provides the optimal microenvironment needful for epididymal sperm maturation. To date, no notions have been reported regarding a putative role of ANKRD31 in the correct BEB formation. In our work, we generated Ankrd31 knockout male mouse model (Ankrd31-/-) and characterized its reproductive phenotype. Ankrd31-/- mice were infertile and exhibit oligo-astheno-teratozoospermia (low number of immotile SPZ with abnormal morphological features). In addition, a complete deregulation of BEB was found in Ankrd31-/-, due to cell-to-cell junction anomalies. In order to suggest that BEB deregulation may depend on Ankrd31 gene deletion, we showed the physical interaction among ANKRD31 and some epithelial junction proteins in wild-type (WT) epididymis. In conclusion, the current work shows a key role of ANKRD31 in the control of germ cell progression as well as sperm and epididymal integrity.